ORIGINAL ARTICLE HUBUNGAN SELF EFFICACY DENGAN SELF ACCEPTANCE PADA ODHA DI JOMBANG CARE CENTER PLUS - Anita Yolandha Yolandha (LPPMK STIKES Widyagama Husada, 2020)
ABSTRACT Yolandha, Anita. 2020. Correlation of Self Efficacy with Self Acceptance of People Living with HIV/AIDS in KDS JCC+ Jombang. Thesis. Nursing Study Program of Widyagama Husada Health Sciences College Malang. Advisors: 1) dr. Wira Daramatasia., M. Biomed. 2) Miftakhul Ulfa., S.Kep., Ns., M.Kep. Background: Good self efficacy is an important component that must be owned by every individual, especially PLWHA in order to be able to run their lives well. If PLWHA have good self efficacy, PLWHA will learn and be able to understand the situation that is happening to them. Objectives: To find out the correlation of self efficacy and self acceptance of people with HIV / AIDS. Research Methods: The design of this study was analytical survey with cross-sectional approach. It was conducted in Jombang Care Center Plus (JCC+) peer support community. There were 55 respondents taken by non probability sampling with purposive sampling technique which met the inclusion and exclusion criteria. Data was collected using (HIV-SE) and self acceptance. Data was analyzed using Somers’d test. Results: The majority of PLWHA have good self efficacy 32 (58.2%) respondents, and self acceptance was enough as many as 36 (65.5%) respondents. The significance value obtained p value 0.001. Conclusion: There is a relationship between self efficacy and self acceptance in people with HIV / AIDS (PLWHA) because the significance value is 0.001 (> 0.05). Suggestion: JCC+ peer support community should continue to provide support for PLWHA in order to maintain their quality of life References : 65 references (1995 – 2020) Keywords : HIV/AIDS, self efficacy, self acceptance, JCC+.